Optimizing Teacher Assistance In Mathematics Learning Through Scaffolding Thresholds - Iis Sugiati; Sri Rahayuningsih; Anton Prayitno (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2025)
A problem in learning mathematics in the classroom is that there are no clear guidelines on when teacher assistance needs to be given, maintained, or stopped. This lack of clarity risks causing disproportionate assistance, either in the form of over-scaffolding which creates learner dependence, or under-scaffolding which inhibits concept understanding. This study aims to identify and examine in depth the threshold for providing scaffolding by teachers in mathematics learning, based on the Zone of Proximal Development (ZPD) theory. The approach used was descriptive qualitative with the subject of six students in class XI at SMK Ahmad Yani Jabung who were selected based on the category of high, medium and low academic ability. Data were obtained through observation of learning activities, in- depth interviews, and document analysis of students' work, and analyzed through the stages of data reduction, presentation, and verification using the Miles and Huberman model. The results showed that the threshold of scaffolding is contextual and dynamic, determined by three main indicators: learners' cognitive responses, the level of dependence on assistance, and verbal and nonverbal expressions. The process of providing assistance includes three stages, namely initial assessment, implementation of scaffolding, and gradual reduction of assistance. The conclusion of this study emphasizes the importance of adjusting teacher interventions according to learners' ZPD position, as well as the need for teacher training and the development of ZPD-based adaptive learning models to improve learning effectiveness and encourage learning independence.